Luxury in Sustainability: Designing Eco-Friendly Yet Opulent Interiors - Batul Zehra; Abhinav Tripathi (International Journal of Architectural Design and Planning, 2025)
This report explores the evolving relationship between luxury and sustainability in interior design, challenging the misconception that opulence and environmental responsibility are incompatible. It examines how high-end residential, commercial, and hospitality spaces integrate sustainable materials, energy-efficient technologies, and ethical sourcing to create refined yet eco-conscious interiors. Through detailed case studies, including Bloomberg European Headquarters, Six Senses Zil Pasyon, and Passive House designs, the study highlights innovative approaches to reducing carbon footprints while maintaining exclusivity and sophistication. The research identifies key challenges such as high costs, material sourcing difficulties, and consumer skepticism, alongside emerging solutions like bio fabricated materials, smart energy systems, and AI-driven automation. Additionally, the impact of eco- certifications (LEED, BREEAM, WELL) on the luxury market is assessed, demonstrating how regulatory frameworks are driving sustainable transformation. Findings suggest that sustainable luxury is not just a passing trend but a fundamental shift in design philosophy, with increasing consumer demand shaping the future of high- end interiors. The report concludes with practical recommendations for designers, emphasizing the importance of biophilic design, circular economy principles, and technological innovation in creating environmentally responsible yet elegant spaces. This study serves as a valuable resource for interior designers, architects, and industry professionals seeking to balance luxury with sustainability in a rapidly evolving market.
Keywords: Biophilic Design; Green architecture; Sustainable luxury; eco-friendly interiors; energy efficiency